RESULTS OF HOSPITAL USE OF RECOMBINANT NON-IMMUNOGENIC STAPHYLOKINASE IN PATIENTS WITH ST-ELEVATED MYOCARDIAL INFARCTION - V. B. Kostogryz (Racionalʹnaâ Farmakoterapiâ v Kardiologii, 2017)
Aim. To assess effectiveness and safety of the hospital use of recombinant non-immunogenic staphylokinase in patients with acute  ST-elevated myocardial infarction (STEMI).Material and methods. Recombinant non-immunogenic staphylokinase was administered during in-hospital stage of treatment of 93 patients with acute STEMI, followed by clinical and electrocardiographic assessment and angiographic verification of the degree of blood flow in the infarct-related coronary  artery. Hemorrhagic complications, allergic reactions, and hospital mortality were also considered.Results. When monitoring electrocardiogram after 90 minutes from the first bolus of recombinant non-immunogenic staphylokinase, the decrease of ST segment by 50% to the isoline was found in 93.5% of patients. Intracranial and extra brain major and small bleedings were not observed, as well as allergic reactions. In the group of patients who underwent coronary  angiography (n=15), antegrade blood flow TIMI 3 was visualized in 100% of cases. Hospital mortality was 6%.Conclusion. Modern thrombolytic drug of recombinant non-immunogenic staphylokinase demonstrated high effectiveness in recovery of blood flow in the infarct-related coronary  artery,  hemorrhagic safety,  and easy to use in the bolus administration.